ELISA and co-agglutination test for detection of K88ac fimbriae in Escherichia coli strains - Barman, N N; Sharma, D K; Rahman, H; Borah, P; Cox, E (The Indian Journal of Animal Sciences, 2012)
ELISA and co-agglutination test were used to detect K88ac fimbriae in the cell free extract of Escherichia coli strains. of 78 isolates recovered from diarrhoeic piglets 45 (57.7%) in ELISA and 38 (48.7%) in co-agglutination te were identified as K88ac positive E.coli. Among the Ecoli isolates the most commonly involved serogroups (08, 0147, 01489, 0157) in piglet diarrhoea were characterized as K88ac bearing E. coli.